ANALISIS DAMPAK SEKTOR UNGGULAN DALAM PERTUMBUHAN EKONOMI KABUPATEN BREBES - Aprilia Rahmasari (Universitas Nias Raya, 2026)
Brebes Regency experiences a gap between the potential and actual performance of its leading sectors, necessitating further identification to determine which sectors truly possess comparative and competitive advantages. This aligns with Law No. 23 of 2014 on Regional Government, which states that regional development should be based on the region's leading potentials. This study aims to identify the leading economic sectors in Brebes Regency by combining Location Quotient (LQ), Shift Share, and Klassen Typology analyses, and by calculating the multiplier effect of the growth of base sectors on the region’s economic growth. The research employs a descriptive quantitative method using secondary time series data from 2019 to 2023, sourced from Central Java BPS and Brebes Regency BPS. The findings reveal that the leading sectors are Agriculture, Forestry, and Fisheries; Wholesale and Retail Trade, Repair of Motor Vehicles and Motorcycles; Accommodation and Food Service; Education Services; and Other Services. However, a shift is observed where the most prominent and strategic sector for the future is no longer Agriculture, but the Manufacturing Industry sector.